Leber Hereditary Optic Neuropathy: Review of Treatment and Management - Hage, Rabih; Vignal-Clermont, Catherine (Frontiers in Neurology, 2021)
Leber’s hereditary optic neuropathy (LHON) is a maternally inherited mitochondrial disease that specifically targets the retinal ganglion cells by reducing their ability to produce enough energy to sustain. The mutations of the mitochondrial DNA that cause LHON are silent until an unknown trigger causes bilateral central visual scotoma. After the onset of loss of vision, most patients experience progressive worsening within the following months. Few of them regain some vision after a period of approximately one year. Management of LHON patients has been focused on understanding the triggers of the disease and its pathophysiology to prevent the onset of visual loss in a carrier. Medical treatment is recommended once visual loss has started in at least one eye. Research evaluated drugs that are thought to be able to restore the mitochondrial electron transport chain of the retinal ganglion cells. Significant advances were made in evaluating free radical cells scavengers and gene therapy as potential treatments for LHON. Although encouraging, the results of clinical trial have been mixed in stopping the worsening of visual loss. In patient with chronic disease of over 1 year, efficient treatment that restores vision is yet to be discovered. In this review, we summarize the management strategies for patients with LHON before, during and after the loss of vision, explain the rationale and effectiveness of previous and current treatments, and report findings about emerging treatments.